The Mobile Court Program as an Instrument for Access to Justice in Remote Areas. An Empirical Study of the Religious Court of Labuha - Ahmad Faiz Shobir Alfikri; Maziya Rahma Wahda; Ahmad Zulfi Wahyudi; M. Azam Rahmatullah (Austronesia Akademika, 2025)
Access to justice remains uneven for communities living in remote archipelagic regions, where distance, transport constraints, and administrative barriers limit their ability to obtain formal judicial services. In response to this problem, the Labuha Religious Court has implemented a mobile court program to bring hearings closer to justice seekers. This study aims to examine how the mobile court program is implemented in the jurisdiction of the Labuha Religious Court and to identify the factors that support and hinder its operation. The research uses a qualitative empirical legal method with a socio-legal approach. Data were collected through semi-structured interviews and documentation involving court officials and community members directly connected to mobile court activities, and were analyzed using the Miles and Huberman interactive model. The findings show that mobile court sessions in Kasiruta and Sanana substantially improved access to justice, especially for marriage validation, divorce by talaq, contested divorce, and guardianship cases. The program was supported by strong institutional commitment, inter-agency collaboration, and active community participation. However, its implementation was constrained by difficult geography, weather uncertainty, limited transportation, and incomplete administrative documents among justice seekers. In conclusion, the mobile court program functions as an effective instrument for expanding inclusive judicial services in remote areas across dispersed island communities.